Biomarkers of Stress in Companion Animals - Gazzano, Angelo; Ogi, Asahi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The welfare of an individual could be severely affected by stressful events. Mainly for this reason, the scientific community is interested in finding specific and quantifiable characteristics which could indicate or predict specific signs of acute or chronic stress exposure. The aim of this reprint is to reflect this interest in the field of companion animal physiology. The authors engaged in publishing this reprint are experts in the multiple mechanisms involved in stress response, including the detection of behavioral and physical signs which can be measured through biological indicators of homeostasis displacement. The editors strongly believe this topic will be of interest not only to researchers in this field, but also to dog trainers, dog shelter workers and veterinary behaviorists.